Ethical Consideration in Business Negotiations: Balancing Integrity and Success - POURSAFAR, MOHAMMADREZA (İstanbul Kültür Üniversitesi, 2025)
Business negotiations are integral to shaping commercial relationships, defining contract terms, and ensuring mutually beneficial outcomes. However, the ethical complexities inherent in negotiation processes often challenge organizations as they strive to balance integrity with achieving strategic advantages. This thesis explores the ethical considerations in business negotiations by analysing both successful and failed corporate practices through a secondary qualitative approach. The study focuses on key ethical themes, including transparency, honesty, Corporate Social Responsibility (CSR) integration, deception, manipulation, and coercion. The research employs thematic analysis to examine case studies from diverse industries, featuring ethical successes such as Toyota, Unilever, and Patagonia, alongside ethical failures like Enron, Volkswagen, and Wells Fargo. The findings demonstrate that ethical negotiation practices, particularly those grounded in transparency, honesty, and CSR, foster stakeholder trust, long-term relationship sustainability, and competitive advantage. In contrast, unethical practices driven by deception and coercion result in reputational damage, financial loss, and legal consequences. The study also highlights the strategic integration of CSR as a vital framework that not only upholds moral standards but also strengthens business resilience and stakeholder engagement. The analysis reveals that ethical negotiation aligns with deontological ethics and virtue ethics, emphasizing duty, integrity, and responsible leadership. Conversely, unethical practices reflect a utilitarian misjudgement where short-term gains overshadow long- term sustainability. The study concludes that embedding ethical frameworks within negotiation practices is crucial for building resilient business models and maintaining stakeholder confidence. Recommendations include integrating ethics training, enhancing CSR-driven negotiation policies, fostering ethical leadership, and establishing transparent accountability mechanisms. By viewing ethical negotiation not as a constraint but as a strategic asset, organizations can secure sustainable growth and upload their moral responsibilities in the global marketplace.
Keywords: Ethical Negotiation; Business Ethics; Corporate Social Responsibility (CSR); Transparency in Negotiation; Honesty in Business Practices; Leadership in Ethical Negotiation; Sustainable Business Relationships; Unethical Negotiation Consequences